The Key Importance of Screening Underprivileged People in Order to Achieve Global Hepatitis Virus Elimination Targets - Laura Gragnani; Monica Monti; Irene De Giorgi; Anna Linda Zignego (Viruses)
Chronic hepatitis B (HBV), alongside hepatitis D virus (HDV) super-/co-infection and chronic hepatitis C (HCV), are major contributors to cirrhosis, end-stage liver disease, hepatocellular carcinoma (HCC), and liver-related mortality. Despite significant progress in antiviral treatments and HBV vaccination, viral hepatitis remains a global health burden. Vulnerable populations, such as those experiencing homelessness, migrants, and economically disadvantaged groups, are disproportionately impacted by these infections, often facing barriers to care and exclusion from traditional health systems. This leads to undiagnosed cases and ongoing transmission, undermining global efforts to eliminate HBV and HCV by 2030, as outlined by the World Health Organization (WHO). Recent studies highlight the importance of tailored interventions to address health inequalities. For instance, on-site community-based screening initiatives targeting marginalized groups have shown promise, achieving higher linkage to care rates without monetary incentives. These approaches not only enhance diagnosis but also facilitate integration into healthcare systems, addressing both public health and social disparities. This review underscores the need for targeted strategies to promote the early detection and management of HBV and HCV in underserved populations. Such efforts are critical to advancing the WHO’s elimination goals, improving health outcomes, and addressing the broader social determinants of health.